2020
DOI: 10.1001/jamanetworkopen.2020.6752
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Health Information Technology–Related Outpatient Diagnostic Delays in the US Veterans Affairs Health Care System

Abstract: IMPORTANCE Diagnostic delay in the outpatient setting is an emerging safety priority that health information technology (HIT) should help address. However, diagnostic delays have persisted, and new safety concerns associated with the use of HIT have emerged. OBJECTIVE To analyze HIT-related outpatient diagnostic delays within a large, integrated health care system. DESIGN, SETTING, AND PARTICIPANTS This cohort study involved qualitative content analysis of safety concerns identified in aggregated root cause an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 74 publications
(181 reference statements)
0
17
0
Order By: Relevance
“…A full-text review of these articles determined that 11 explicitly documented a relationship between EHR use and diagnostic error. [15][16][17][18][19][20][21][22][23][24][25] The summary of study characteristics for these 11 articles can be found in Table 2. Most articles (n = 9; 81.8%) focused on diagnostic errors in ambulatory or primary care settings.…”
Section: Summary Of Reviewed Articlesmentioning
confidence: 99%
“…A full-text review of these articles determined that 11 explicitly documented a relationship between EHR use and diagnostic error. [15][16][17][18][19][20][21][22][23][24][25] The summary of study characteristics for these 11 articles can be found in Table 2. Most articles (n = 9; 81.8%) focused on diagnostic errors in ambulatory or primary care settings.…”
Section: Summary Of Reviewed Articlesmentioning
confidence: 99%
“…Participants in each room were asked to work on one of 3 feedback interventions we developed from the literature in the problem domain [18][19][20][21][22]. For purposes of our project, we labeled each of the 3 intervention types as follows: "social" (ie, a conversation guide for one's supervisor), "technical" (ie, an electronic data dashboard), and "sociotechnical" (ie, an email message or template).…”
Section: Virtual Roomsmentioning
confidence: 99%
“…Evidence-based strategies to prevent medication errors, failures in teamwork, problems with communication and coordination, and breakdowns in follow-up of test results and referrals have emerged but havebeenimplementedinconsistently. 1,6 Toclosegapsbetweenknowledge and implementation, outpatient practices need dedicated time, training, incentives, and resource support. To enable change, large integrated delivery systems could leverage their infrastructure to create ambulatorysafetyprogramsandbecomelearningcentersthattestand implement safety strategies.…”
Section: Practice Milestonesmentioning
confidence: 99%